Local wisdom tradition of maintenance of the upstream river - Aryani, Ine Kusuma; Kertopati, R. Beny Wijarnako (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Various local wisdoms are used as the center of life, obeyed, revered and given a special place by every individual. Until now, these individuals still adhere to local wisdom passed down from generation to generation as the community's cultural heritage, namely the tradition of protecting the upper reaches of the Logawa River for the people of Baseh Village. A form of local wisdom in improving community welfare by relying on the values of ancestral teachings. The aim of this research is to examine local wisdom in the maintenance and utilization of the upstream area of the Logawa River in Baseh Kedungbanteng village, Banyumas Regency, to reveal cultural character biases related to human actions related to the natural surroundings where the community resides. This research uses a case study method which focuses on one particular object to be used as a case. Baseh Village, Kedungbanteng District. Data was obtained through studying the interconnectedness of evidence from several data sources at once, namely documents, recordings, observations, open, focused and structured interviews, as well as documentation studies. The results of the research show that the true meaning is revealed, namely increasing the welfare of society both economically and for the common good. their daily needs. Research on local wisdom traditions in upstream river maintenance can be an important basis for development policies and sustainable practices in managing river ecosystems throughout the world.